Histological and radiographic evaluation of the muscle tissue of rats after implantation of bone morphogenic protein (rhBMP-2) in a scaffold of inorganic bone and after stimulation with low-power laser light - Bengtson Antonio; Bengtson Nadya; Bengtson Camilla Regina; Mendes Fausto; Pinheiro Sérgio (Wolters Kluwer Medknow Publications, 2010)
Objective: The present study histologically and radiologically evaluates the muscle tissue of rats after implantation of bone morphogenic protein (rhBMP-2) in a natural inorganic bone mineral scaffold from a bull calf femur and irradiation with low-power light laser. Materials and Methods: The right and left hind limbs of 16 rats were shaved and an incision was made in the muscle on the face corresponding to the median portion of the tibia, into which rhBMP-2 in a scaffold of inorganic bone was implanted. Two groups of limbs were formed: control (G1) and laser irradiation (G2). G2 received diode laser light applied in the direction of the implant, at a dose of 8 J/cm2 for three minutes. On the 7th, 21st, 40th and 112th days after implantation, hind limbs of 4 animals were radiographed and their implants removed together with the surrounding tissue for study under the microscope. The histological results were graded as 0=absence, 1=slight presence, 2=representative and 3=very representative, with regard to the following events: formation of osteoid structure, acute inflammation, chronic inflammation, fibrin deposition, neovascularization, foreign-body granuloma and fibrosis. Results: There were no statistically significant differences in these events at each evaluation times, between the two groups (P > 0.05; Mann-Whitney test). Nevertheless, it could be concluded that the natural inorganic bone matrix with rhBMP-2, from the femur of a bull calf, is a biocompatible combination. Conclusions: Under these conditions, the inductive capacity of rhBMP-2 for cell differentiation was inhibited. There was a slight acceleration in tissue healing in the group that received irradiation with low-power laser light.